Development and Validation of the Computerized Family Relations Test for Children - Skoczeń, Ilona; Cieciuch, Jan; Oud, Johan H. L.; Welzen, Kai (Frontiers in Psychology, 2015)
The aim of the present study was to develop and investigate the psychometric properties of the Computerized Family Relations Test (CFRT) for children. This test assesses the quality of family relationships with the mother and father from a child’s perspective. The CFRT consists of six scales relating to control (Restrictiveness and Justice), and support (Affection, Vulnerability, Acknowledgment, and Trust) within the family relationships. CFRT is an innovative approach to the Dutch Nijmegen Family Relations Test (NFRT) developed by Oud and Welzen (1989). The administration of the test has been computerized and graphical representations of female and male silhouettes were included to facilitate the child’s parental identification. In total, 404 primary school children, aged 8 to 13 years (M = 11.0; SD = 1.17), took part in this study. The CFRT’s reliability was assessed by McDonald’s omega coefficients, and ranged from 0.71 to 0.86, except for Vulnerability which achieved the lowest reliability 0.57 for mothers’ ratings and 0.56 for fathers’ ratings. The test–retest procedure revealed higher stability for the ratings on father-child relationships of 0.71 compared to mother-child relationships of 0.67. Confirmatory factor analysis indicated that a six-factor model provided an adequate fit. Measurement invariance across the children’s assessments of the quality of family relationships was achieved. The construct validity of CFRT was assessed by examining differences in the child’s ratings of the relationships with the mother and father, the child’s gender, and associations of CFRT scales with other variables such as depression, anxiety symptoms, and prosocial behavior.